Hubungan Evapotranspirasi, Hujan dan Elevasi Muka Air Tanah pada Lahan Gambut Tropis Sebagai Awal Penentuan Kondisi Lahan Basah - Nilna Amal (School of Postgraduate Studies, Diponegoro Univer, 2023)
The relationship between parameters in wetlands, especially peatlands, as a part of the analysis is interesting to study. The analysis is expected to show the condition of the peatland or the state of the wetlands in general. The water table elevation (WTE) is measured daily, so to compare it with evapotranspiration and rain, daily values for these two parameters are also required. The study was conducted between June-July and August 2022 on shallow peatlands in Gambut District, Banjar Regency, South Kalimantan Province. Evapotranspiration in this study was calculated using the Hargreaves and Modified Hargreaves method which presents a daily evapotranspiration calculation. The methods only depend on the maximum and minimum temperature, the number of outer space radiation whose magnitude depends on its location on the earth's surface, and the time when the research is conducted. The results showed that the highest daily evapotranspiration value generally occurred in August, which was in accordance with previous studies, but the magnitudes were different. The daily evapotranspiration value in this study ranged from 0.5 mm to 1.8 mm, while previously, the values were greater. WTE values show a strong relationship with rainfall, where rainfall increases the WTE value, and conversely, the absence causes the WTEs to decrease gradually. In general, the condition of the peatlands in the study area based on the groundwater elevation conditions still looks quite good with a fast response to rain. The relationship of evapotranspiration with rain and water table elevation cannot be clearly seen in this study because alterations in rainfall and WTE do not directly indicate changes in evapotranspiration values, so a more extended study covering other months and more in-depth covering parameters and other methods is needed to draw valid conclusions more accurate.